1998
DOI: 10.1023/a:1007965026738
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Catechol and endogenous catechol derivatives are readily methylated by catechol O-methyltransferase (COMT). In contrast, many catechol derivatives possessing electronegative substituents are potent COMT inhibitors. The X-ray structure of the active site of COMT suggests that the methylation involves a lysine as a general base. The lysine can activate one of the catecholic hydroxyl groups for a nucleophilic attack on the active methyl group of the coenzyme S-adenosyl-L-methionine (AdoMet). We studied the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The correct protonation state of catechol bound to COMT has been a subject of discussion. , Since the p K a of this substrate in aqueous solution is 9.9, catechol predominantly binds in the neutral form to the enzyme. Supported by experimental studies on methylase models, it was suggested that COMT effects the methyl transfer reaction via general base catalysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correct protonation state of catechol bound to COMT has been a subject of discussion. , Since the p K a of this substrate in aqueous solution is 9.9, catechol predominantly binds in the neutral form to the enzyme. Supported by experimental studies on methylase models, it was suggested that COMT effects the methyl transfer reaction via general base catalysis.…”
Section: Methodsmentioning
confidence: 99%
“…Similar base catalysis function of lysine residues has been suggested for other enzymatic systems . Semiempirical gas phase model calculations of the active site even predict doubly ionized catechol to be most stable when bound to COMT, but should be interpreted with caution because of the neglect of solvation yielding unrealistically high energy differences between protonation states. There are two reasons that make it unlikely that catechol is bound to the enzyme in the dianionic form.…”
Section: Methodsmentioning
confidence: 99%
“…Considering a pKa1 value of around 9 for catechols [41] and experiments being performed at pH 8, the neutral species would prevail. However, we used the monodeprotonated species for our calculations based on the following arguments: inhibition mechanism of 2-CE involves chelation of the Mn 2 + catalytic ions [36] and AMJ-147 presents a catechol group; catechol metal chelation within active sites involves H-bonding, even proton abstraction from hydroxyl groups by neighbouring amino acid residues which enhances negative partial charge over oxygen atoms as it occurs in catecholo-methyltransferases [42,43] and classical molecular dynamics (MM) do not account for the latter effect as quantum mechanics (QM) or hybrid QM/MM do. For comparison purposes, AMJ-147 was also simulated in its neutral state.…”
Section: Protonation States Of 2-ce and Amj-147mentioning
confidence: 99%